2019
DOI: 10.2319/021619-116.1
|View full text |Cite
|
Sign up to set email alerts
|

Overbite depth indicator and anteroposterior dysplasia indicator cephalometric norms for African Americans

Abstract: Objectives: To examine normal Overbite Depth Indicator (ODI) and Anteroposterior Dysplasia Indicator (APDI) values in African Americans and to compare them with mean values from white patients. Secondary aims were to compare mean ODI and APDI values among different age, gender, and combined age-gender groups in African American patients. Materials and Methods: Lateral cephalometric radiographs of 160 African American patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
(42 reference statements)
0
2
0
1
Order By: Relevance
“…It was found that African Americans have significantly lower ODI and APDI (70.9° and 78.1°, respectively) (p<0.0001) compared to the white population. In addition, no sex differences were found in the study groups [22].…”
Section: Results Discussionmentioning
confidence: 74%
“…It was found that African Americans have significantly lower ODI and APDI (70.9° and 78.1°, respectively) (p<0.0001) compared to the white population. In addition, no sex differences were found in the study groups [22].…”
Section: Results Discussionmentioning
confidence: 74%
“…Since Broadbend’s and Hofrath’s introduction of the cephalometric analysis in 1931, many investigators have introduced further measurements and analyses to assess the skeletal or dentoalveolar basis of malocclusion [ 27 , 28 ]. A detailed cephalometric analysis is still an effective tool for the diagnosis and planning of orthodontic treatment.…”
Section: Discussion Of Outcomesmentioning
confidence: 99%
“…Se ha demostrado que medidas como ODI y APDI presentan un alto valor diagnóstico al establecer un vínculo entre la inclinación del plano oclusal y la discrepancia esquelética sagital y vertical. Es por esta razón que se utilizaron para clasificar a los pacientes del presente estudio (13,14,(19)(20)(21).…”
Section: Discussionunclassified